Risk, return & performance evaluation of selected mutual fund schemes – a study on large & mid cap funds - K Bhuva, Krunal; R Bantwa, Ashok (Journal of Management and Science, 2012)
This paper studies the persistence of mutual fund performance. Academic research often focuses on fund returns. This study intends to examine the performance of selected Large cap and Mid cap mutual fund schemes of Indian Mutual fund industry during the study period 2007 to 2011. The performance of selected schemes is evaluated in terms of average returns, systematic risk, and unsystematic risk and by using different measures like: Sharpe, Jenson, Treynor and FAMA. After detailed analysis it is found that except two all the sampled schemes have performed better than market. Supporting the established relationship of high risk - high return, better performing schemes are exposed to higher risk. The findings also revealed that majority of the schemes were adequately diversified and about 60% of the schemes were able to beat the market with help of better stock selection skill of fund managers. Finding from the t-test calculations shows that there is no difference between returns from large cap mid cap mutual funds in long run. From the return comparison of mutual funds and market, in 2008 & 2011 large cap are underperforming than market and in 2011 only mid cap mutual funds are showing less return than market returns.